The Effect Of Interactive Learning Models On Students’ Learning Outcomes In Islamic Religious Education And ETHICS At Senior High School Negeri 1 Girimarto In The 2025/2026 Academic Year - Rahma Eprilya Sholihaha; Maulana Iskandar; Ratih (Jurnal Ilmu Pendidikan dan Sains Islam Interdisipliner, 2025)
This research is based on the low learning outcomes of students due to the use of conventional learning models, which do not involve student activity in the learning process. The learning model that still uses the lecture method, only uses sources from package books so that the lack of class participation is marked by the inability of students to ask questions so that students do not understand the material being taught. The purpose of this study is to determine the influence of interactive learning models on student learning outcomes in PAI and BP subjects at SMAN 1 Girimarto. This study uses a quantitative approach with the Nonequvalent Control Group Design design experiment method. Samples from class X F as experimental class and X G as control class. The research instrument is in the form of a learning outcome test. The results of the study show that there is a significant influence of the use of interactive learning models on student learning outcomes. After being treated with an interactive learning model in the experimental class and given a posttest, the results showed that the average score of the experimental class increased by 81.86 while the control class was 77.14. The initial ability test obtained from the control and experimental class pretest data resulted in a sig value. (2-tailed) by 0.774. The average sample of the experimental class produced sig. (2-tailed) 0.000 with a count of -8.804 and an average of -12.286 indicates that there was a significant improvement in learning outcomes after the application of the interactive learning model to PAI and BP subjects in the experimental class. Based on the N Gain test, there was an influence of the interactive learning model on the learning outcomes of Islamic Religious Education and Ethics at SMAN 1 Girimarto which was evidenced by the average value of N Gain in the experimental class of 0.397 higher than the average value of the control class of 0.257.